Realızıng Good Governance Through Restructurıng Of Regıonal Development Organızatıons In Lombok Central Region - Mujahidin Mujahidin; Arif Darmawan; Rudy Handoko (Cita Konsultindo Research Center, 2023)
Bureaucratic reform requires changes in all aspects of government, from standardization of human resources to governance structures. The aim of this study is to examine the organizational restructuring of regional apparatuses in their efforts to achieve good governance. This descriptive qualitative study uses a phenomenological approach, with primary data collected from FGD interviews with several researchers as well as Central Lombok District officials and observers. The results of the interpretive study analysis can explain that the Central Lombok District Government Bureaucratic Restructuring process that was built has not been able to create a modern bureaucratic structure, and still seems to apply the old bureaucratic structure model. This condition is parallel to the level of progress of society which expects streamlining the domination of the role of the bureaucracy and strengthening community participation in all aspects of life. The relevance of changes to the pillars of good governance can be said that the restructuring of the bureaucracy in the regional apparatus organizations of Central Lombok Regency has not yet led to the development of good governance at the local level. The results of the analysis using the reinventing government approach show that in recommending the desired organizational structure design, the regional apparatus still needs to determine the classification as a framework, namely the line structure, namely the implementing element of the regional government that has the authority to determine policy formulation or implementation of policies (policy application) for the field of duty and units that carry out operational tasks; and staff structure, is an organizational unit that functions to provide support or assistance for the achievement of regional government organizational goals.